The Matrix of the New Covenant for Contextualizing the Gospel Among the Slavic Peoples - Saucy, Mark (Bogoslovskie razmyšlenija, 2003)
The New Covenant, foretold by the prophets of Israel and fully revealed in the apostles’ writings, is the working blueprint for the Church of Jesus Christ. The New Covenant determines both the Church’s nature and mission in the world. Effective ministry of the Church in any surrounding culture depends on the Church working according to her created nature in the New Covenant. The Orthodox cultural milieu of many of the lands of the former Soviet Union calls for a very clear understanding of the New Covenant nature of the Church before «Orthodox» points of contact are attempted in worship and evangelism.